Reproductive profile of captive Sumateran tiger (Panthera tigris sumatrae) - GONO SEMIADI; R. TAUFIQ PURNA NUGRAHA (Society for Indonesian Biodiversity, 2006)
The Sumatran tiger (Panthera tigris sumatrae) is one of several endemic Indonesian wild cat groups which population is critically endangered. A program to increase the population size had been conducted in captivity, especially in the zoo. In order to monitor the captive population and for the means of management in captivity, a logbook data recording system had been developed for individual animals. A compilation data from the Tiger International Stud Book from 1942 to 2000 was analyzed. The extraction data consisted of the reproduction performance of the animals, such as calving pattern, sex ratio, litter size etc. The results showed that mortality of cubs at ≤ 5 months old reached 59%, between 5 and 24 months old was 9.3% and above 24 months was 31.7%. Cubs were born all year round with concentration in July for Europe and North America regions. The mean of first reproductive age was at 4.6 years old (± 2.28), with the mean of the oldest reproductive age was at 8.3 years (± 3.63). Mean litter size was 2.21 cubs from dame born in captivity and 2.45 cubs from dame capture from the wild. Sex ratio of male to female was 53.8:46.2. The average lifespan of adult wild captive tiger was 5108.9 day (± 2365.4) day, while for adult (≥ 24 months of age) captive tiger was 4417.4 day (± 1972.7).© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Sumateran tiger, Panthera tigris sumatrae, reproduction, stud book.